Response of rhizosphere microbial community characteristics and ecosystem multifunctionality to the addition of crude oil in Achnatherum splendens and Pennisetum alopecuroides - Wei, Ying; Zhu, Yukun; Nian, Lili; Yang, Liqun; Yue, Ming; Mao, Zhuxin; Li, Lijuan (Frontiers in Microbiology, 2025)
This study aimed to reveal the effects of crude oil addition on the characteristics of soil microbial communities and ecosystem multifunctionality in Achnatherum splendens and Pennisetum alopecuroides. Specifically, it explored how crude oil addition influences the relationship between soil nutrient regulation, microbial community characteristics, and ecosystem multifunctionality. The results indicated that as crude oil addition increased, the Shannon index and Chao1 index for soil bacteria and fungi in both Achnatherum splendens and Pennisetum alopecuroides increased. Conversely, while the Shannon index for soil archaea in both species increased, the Chao1 index decreased. The ecological network analysis indicated that a strong collaborative relationship existed between species in the soil bacterial communities of Achnatherum splendens and Pennisetum alopecuroides exposed to 10 g/kg crude oil, as well as between species in the soil fungal and archaeal communities of Achnatherum splendens exposed to 40 g/kg crude oil. A strong collaborative relationship was also observed between species in the soil fungal and archaeal communities of Pennisetum alopecuroides exposed to 10 g/kg crude oil. The bacterial and fungal communities exerted a significant direct negative regulatory effect on the soil ecosystem multifunctionality of Achnatherum splendens and Pennisetum alopecuroides, while the archaeal communities had a significant direct positive regulatory effect. Additionally, the multifunctionality index of the soil ecosystem in Achnatherum splendens and Pennisetum showed a significant decline with increasing crude oil addition. This is likely due to the higher toxicity of high-concentration crude oil, which negatively impacts the soil biological community, leading to reduced biodiversity and disruptions in nutrient cycles. This study explores the characteristics of bacterial, fungal, and archaeal communities and ecosystem multifunctionality under different levels of crude oil, which can provide theoretical support for evaluating the restoration of Achnatherum splendens and Pennisetum alopecuroides from crude oil pollution.